The effect of laughter therapy on radiation dermatitis in patients with breast cancer: a single-blind prospective pilot study - Kong, Moonkyoo; Shin, Sung Hee; Lee, Eunmi; Yun, Eun Kyoung (OncoTargets and therapy, 2014)
There have not yet been any published studies on the effects of laughter therapy on radiation-induced dermatitis in breast cancer patients treated with radiotherapy (RT). We assessed the effectiveness of laughter therapy in preventing radiation dermatitis in patients with breast cancer. Thirty-seven patients were prospectively enrolled in this study. Eighteen patients were assigned to the experimental group and the other 19 patients were assigned to the control group. The patients who were assigned to the experimental group received laughter therapy during RT. Laughter therapy was started at the onset of RT and was provided twice a week until completion of RT. The patients who were assigned to the control group only received RT without laughter therapy. The grade of radiation dermatitis was scored by a radiation oncologist who was blinded to subject assignment. The patients' evaluation of pain within the RT field was also assessed. In the experimental group, radiation dermatitis of grade 3, 2, and 1 developed in five (33.3%), five (33.3%), and five patients (33.3%), respectively. In comparison, in the control group, radiation dermatitis of grade 3, 2, 1, and 0 developed in seven (36.8%), nine (47.4%), two (10.5%), and one patient (5.3%), respectively. The experimental group exhibited a lower incidence of grade 2 or worse radiation dermatitis than the control group (33.3% versus 47.4%). The mean maximal pain scores in the experimental and control group were 2.53 and 3.95, respectively. The experimental group complained of less severe pain than the control group during RT. However, these differences were not statistically significant. The results of this study show that laughter therapy can have a beneficial role in preventing radiation dermatitis in patients with breast cancer. To confirm the results of our study, well-designed randomized studies with large sample sizes are required.